A comprehensive approach to modeling musculoskeletal aging and injury: an emphasis on Nrf2-related pathogenesis - Andrie, Kendra M., author; Santangelo, Kelly S., advisor; Hamilton, Karyn, committee member; Goodrich, Laurie, committee member; Podell, Brendan, committee member; Muñoz Gutiérrez, Juan, committee member; Miller, Benjamin, committee member (Colorado State University. Libraries, 2021)
Osteoarthritis (OA) is a degenerative joint disease that affects over 730 million people globally, over 30 million Americans, and is the leading cause of disability in adults. The underlying pathogenesis is multifactorial and largely undetermined, with a variety of cellular pathways and risk factors contributing to disease onset and progression. The crux of this work is that downregulation in nuclear factor erythroid-2 related factor-2 (Nrf2)-signaling in musculoskeletal tissue serves as a central driver for persistent low-grade inflammation, dysregulation of redox homeostasis, mitochondrial dysfunction, and protein dyshomeostasis, all of which contribute to OA progression. To explore the role of this pathway in OA, we utilized the Hartley OA-prone guinea pig model, which develops naturally occurring idiopathic disease with pathology that mimics human disease. My global hypothesis is supported by preliminary data that demonstrates that aging Hartley guinea pig knee joint tissues have decreased expression of Nrf2 mRNA and protein, which coincides with disease onset and remains decreased throughout OA progression. We investigated the utility of a novel nutraceutical and Nrf2-activator in delaying both the onset and progression of idiopathic OA in this model. The ultimate goal of this work is to (1) identify key molecular pathways involved in the etiopathogenesis of OA, with a particular focus on the contribution of the Nrf2 pathway; (2) investigate the utility of a novel nutraceutical and Nrf2-activator in delaying the onset and/or progression of OA in the Hartley guinea pig, and (3) examine the effects of Nrf2-activation on long bone strength. The inclusion of a musculoskeletal condition beyond OA was also pursued; as such, the clinical and histologic manifestations of a novel rectus femoris myotendinous junction injury model was characterized in rats. Ultimately, this work seeks to advance the understanding of musculoskeletal aging and injury through the analysis of key structural and functional outcome measures to further develop appropriate therapeutic targets for disease prevention and treatment.